ANALISIS RISIKO KERUSAKAN PADA ALAT BERAT GRAB DENGAN METODE FAILURE MODE AND EFFECT ANALYSIS (Study Kasus: PT SIAM MASPION TERMINAL GRESIK) - Achmad Fany Rislamy; Nina Aini Mahbubah; Dzakiyah Widyaningrum (Universitas Riau Kepulauan, 2020)
Preventive maintenance is considered as keypoint in maintenace management in order to maintain logistics’ steadiness along with pre and post production process. PT. Siam Maspion Terminal is one of the leading port’s service company which is provide logistics services on terminal port. Grab heavy eguipment is considered as the main equipment during looading and unloading process. Initial instigation found that inspite of periodically maintenance have been implemented, however, a high number of machine’s downtine have been identified. This study aims to analyze the cause and effect risk failure of grab’s components in order to mitigate alternative preventive maintenance using the FMEA approach. This research begins with downtime identification of five types of Grab heavy equipment, followed by identify the cause and effect such failure to determine ranking values based on the severity, frequency of occurrence, and detection. A number of espondents from the maintenance department were chosen as expert who filled out the FMEA questionnaire. This study found that there are six Grab components which are identified as critical component from Grab no 2 and Grab no 5. It was found that two highest failure risk are pulley and axle components. Regular maintenace recommendations based on these critical failure components are recommended in order to prevent such failure occur in the future.